Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam - Nguyen, Lien Thi Phuong; Vu, Thuong Thi; Daglio, Anthony; Wiśniowski, Bogdan (Zootaxa, 2019)
A taxonomic review of the genus Vespula Thomson in Vietnam is reported. Three species are recorded: V. flaviceps (Smith, 1870), V. koreensis (Radoszkowski, 1887), and V. orbata (Buysson, 1902). Of these, V. flaviceps is newly recorded from Vietnam. Distribution records of all three species and an identification key to species based on morphological characters are presented. Vespula koreensis is distributed from high (Cao Bang, Vinh Phuc, Quang Tri) to lower areas (Thai Nguyen, Tuyen Quang, Lang Son, Bac Giang), while the other two species are distributed in high mountainous areas of the northern and central regions of Vietnam such as in Cao Bang, Lao Cai, Son La, Phu Tho, Vinh Phuc, Quang Tri and Quang Nam provinces.